Mechanical and Physical Properties of Polyester Polymer Concrete Using Recycled Aggregates from Concrete Sleepers - Francisco Carrión; Laura Montalbán; Julia I. Real; Teresa Real (The Scientific World Journal)
Currently, reuse of solid waste from disused infrastructures is an important environmental issue to study. In this research, polymer concrete was developed by mixing orthophthalic unsaturated polyester resin, artificial microfillers (calcium carbonate), and waste aggregates (basalt and limestone) coming from the recycling process of concrete sleepers. The variation of the mechanical and physical properties of the polymer concrete (compressive strength, flexural strength, modulus of elasticity, density, and water absorption) was analyzed based on the modification of different variables: nature of the recycled aggregates, resin contents (11 wt%, 12 wt%, and 13 wt%), and particle-size distributions of microfillers used. The results show the influence of these variables on mechanical performance of polymer concrete. Compressive and flexural strength of recycled polymer concrete were improved by increasing amount of polyester resin and by optimizing the particle-size distribution of the microfillers. Besides, the results show the feasibility of developing a polymer concrete with excellent mechanical behavior.